Psychological characteristics of group cohesion athletes. - Sheriff Sarhan (Kharkov National Pedagogical University, 2011)
The basic components of group cohesion in sport teams. An analysis of publications on cohesion within the groups where an interconnection of individual goals of each participant group with common goals and the end result of teamwork. The concept of harmony in the team sports, where the rate of group cohesion is dependent on such integrative index as psychological climate. It is established that a number of athletes to achieve high results require high cohesion, unity, value-normative orientation, deep identification and responsibility for the results of the joint group activities.